Neuromuscular control during the bench press movement in an elite disabled and able-bodied athlete - Golas, A.; Zwierzchowska, A.; Maszczyk, A.; Wilk, M.; Stastny, P.; Zajac, A. (Journal of Human Kinetics, 2017)
The disabled population varies significantly in regard to physical fitness, what is conditioned by the damage to the locomotor system. Recently there has been an increased emphasis on the role of competitive sport in enhancing health and the quality of life of individuals with disability. One of the sport disciplines of Paralympics is the flat bench press. The bench press is one of the most popular resistance exercises used for the upper body in healthy individuals. It is used not only by powerlifters, but also by athletes in most strength-speed oriented sport disciplines. The objective of the study was to compare neuromuscular control for various external loads (from 60 to 100% 1RM) during the flat bench press performed by an elite able-bodied athlete and an athlete with lower limb disability. The research project is a case study of two elite bench press athletes with similar sport results: an able-bodied athlete (M.W., age 34 years, body mass 103 kg, body height 1.72 m, 1RM in the flat bench press 200 kg) and a disabled athlete (M.T., age 31 years, body mass 92 kg, body height 1.70 m, 1RM in the flat bench press 190 kg). The activity was recorded for four muscles: pectoralis major (PM), anterior deltoid (AD), as well as for the lateral and long heads of the triceps brachii (TBlat and TBlong). The T-test revealed statistically significant differences between peak activity of all the considered muscles (AD with p = 0.001; PM with p = 0.001; TBlat with p = 0.0021 and TBlong with p = 0.002) between the 2 athletes. The analysis of peak activity differences of M.W and M.T. in relation to the load revealed statistically significant differences for load changes between: 60 to 100% 1RM (p = 0.007), 70 to 100% 1RM (p = 0.016) and 80 to 100% 1RM (p = 0.032). The flat bench press performed without legs resting firmly on the ground leads to the increased engagement of upper body muscles and to their greater activation. Isolated initial positions can be used to generate greater engagement of muscle groups during the bench press exercise and evoke their higher activation.